Draft Annual Plan 1978-79 Part I Government of Assam - Planning Commission (Planning Commission, 1978)
The, total anticipated expenditure for the State Annual Plan 1977-78 is expected to be of the order of Rs. 117.90 crores and the expenditure under MNP at Rs.14.10 crores as detailed in the Statement of Outlays and expenditure (Summary Statement GN-I). It is expected that the physical targets set forth under the different sectors of development for 1977-78 will be fully achieved.
Government of Assam, Planning and Development Department